An ecological framework of neophobia: from cells to organisms to populations. (10th October 2019) - Crane, Adam L.; Brown, Grant E.; Chivers, Douglas P.; Ferrari, Maud C. O.
ABSTRACT: Neophobia is the fear of novel stimuli or situations. This phenotype has recently received much ecological attention, primarily in the context of decision making. Here, we explore neophobia across biological levels of organisation, first describing types of neophobia among animals and the underlying causes of neophobia, highlighting high levels of risk and uncertainty as key drivers. We place neophobia in the framework of Error Management Theory and Signal Detection Theory, showing how increases in overall risk and uncertainty can lead to costly non‐responses towards novel threats unless individuals lower their response threshold and become neophobic. We then discuss how neophobic behaviour translates into population and evolutionary consequences before introducing neophobia‐like processes at the cellular level, where some phenomena such as allergy and autoimmunity can parallel neophobic behaviour. Finally, we discuss neophobia attenuation, considering how a sudden change in the environment from dangerous to safe can lead to problematic over‐responses (i.e. the 'maladaptive defensive carry‐over' hypothesis), and discuss treatment methods for such over‐responses. We anticipate that bridging the concept of neophobia with a process‐centered perspective can facilitate a transfer of insight across organisational levels.